STRATEGI GURU DALAM PEMBENTUKAN KARAKTER SISWA KELAS III PADA PEMBELAJARAN IPAS DI SD NEGERI 204 PALEMBANG - Alfarizi, Rifqi; Idris, Muhamad; Budi Irawan, David (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies used by teachers in building the character of third-grade students during IPAS (Natural and Social Sciences) learning at SD Negeri 204 Palembang. This study employed a qualitative approach with a descriptive method. The research participants consisted of the principal, third-grade teacher, and students. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The results showed that teachers applied several strategies in character building, including role modeling, habituation, integration of character values into IPAS learning, the use of active learning methods, and reinforcement and motivation. These strategies focused on developing students’ discipline and responsibility. Their implementation was reflected in students’ habits of obeying classroom rules, arriving on time, completing assignments, and actively participating in learning activities. Although some students still required further guidance, the strategies implemented by the teacher contributed positively to students’ character development.